Tracing the Relational : The Archaeology of Worlds, Spirits, and Temporalities - Skousen, B. Jacob, 1981-; Skousen, B. Jacob, 1981-; Buchanan, Meghan E., 1981-; Buchanan, Meghan E., 1981- (Book collections on Project MUSE., 2015)
"Tracing the Relational examines the recent emergence of relational ontologies in archaeological interpretation and explores how using this perspective can help archaeologists better understand the past. Traditional representational approaches reflect modern or Western perspectives, which focus on the individual and see the world in terms of dichotomies that separate culture and nature, human and object, sacred and secular. In contrast, ancient societies saw themselves as connected to and entangled with other human and nonhuman entities. Contributors argue that to gain deeper insight into how people in the ancient world lived, experienced, and negotiated their lives archaeologists must explore the myriad relationships and entanglements between humans and other beings, places, and things. As contributors unravel these relationships, they demonstrate that movement is an inherent feature of these relational webs and is the driving force behind a continually shifting reality. Chapters focus on various regions and time periods throughout the Americas, tracing how movements between otherworldly dimensions, spirits and deities, and temporalities were integral to everyday life"--